KOMPOSISI TANAH UNTUK TEKNIK REPRODUKSI KERAMIK DI SENTRA GERABAH PAGERJURANG KLATEN - Arif Suharson dan Dwita Anja Asmara (Corak : Jurnal Seni Kriya, 2012)
The study aims to identify ideal formula of clay compositionas the main material of functional ceramics produced in cylindrical and non-cylindrical shapes with the hand and feet rotating techniques.The rotating technique has some limitations because it cannot be employed in the making of non-cylindrical shapes.Even worse that the existing rotating techniques have failed to produce high-quality ceramics as demanded by consumers. Preciseness ofsize, shapes, and thickness of ceramic wall is a great concern and thus it is necessary to have the analysis of technical aspects and raw materials.The ceramic products from Pagerjurang have attracted many foreign consumers. The products have to meet the specified standard of quality including thematerial,model/shape, size, and timeliness of order accomplishment. Reproduction technique is the appropriate solution to have the desired shapes, sizes, and thickness of ceramic wall. Manual experiments are required to test the quality of clay whilelaboratory testing is needed to test the chemical elements.The ideal formula of clay composition as the main material of ceramic products in Pagerjurang will enable ceramic reproduction through single casting, multiple casting, and slip castingso that the expected export quality standard can be met.In this way, the preciseness of shape, size, and thickness of ceramic wall as well as diversified non-cylindrical products requested by consumers can be ensured. Thus it will provide better economic advantages for the ceramic artisans in Pagerjurang.Key words:ceramic of pagerjurang,reproduction technique